The Influence of Science Modules Integrated with Local Wisdom on Enhancing Scientific Literacy: A Systematic Literature Review - Salwa Nur Sapiatun Nakjah; Melani Aulia Khatami (Indonesian Journal of Teacher Education, 2026)
This study is motivated by the importance of improving students’ scientific literacy through science learning that is contextual and relevant to everyday life. The Merdeka Curriculum emphasizes student-centered learning and the integration of local contexts, making ethnoscience-based science modules a promising alternative. This study aims to analyze the trends and feasibility of using science modules integrated with local wisdom to enhance students’ scientific literacy. The method employed is a qualitative approach using a Systematic Literature Review (SLR), conducted through the stages of identification, selection, and analysis of scientific articles published between 2016 and 2026. Out of 50 identified articles, 15 met the inclusion and exclusion criteria and were selected for further analysis. The findings indicate that ethnoscience-based science modules are consistently considered valid, practical, and effective in improving scientific literacy. This improvement is evidenced by pretest and posttest results with N-Gain scores ranging from moderate to high, as well as positive feedback from students. The integration of local wisdom has been proven to make learning more contextual, enhance conceptual understanding, and develop critical thinking and science process skills. Therefore, ethnoscience-based modules play a strategic role in supporting meaningful science learning.